Crystal structure and molecular characterization of NADP+-farnesol dehydrogenase from cotton bollworm, Helicoverpaarmigera. (August 2022) - Kumar, Rakesh; Das, Joy; Mahto, Jai Krishna; Sharma, Monica; Vivek, Shah; Kumar, Pravindra; Sharma, Ashwani Kumar
Abstract: Farnesol dehydrogenase (FDL) orchestrates the oxidation reaction catalyzing farnesol to farnesal, a key step in the juvenile hormone (JH) biosynthesis pathway of insects and hence, represents a lucrative target for developing insect growth regulators (IGRs). However, information on the structural and functional characterization of JH-specific farnesol dehydrogenase in insects remains elusive. Herein, we identified a transcript that encodes farnesol dehydrogenase ( HaFDL ) from Helicoverpa armigera, a major pest of cotton. The investigations of molecular assembly, biochemical analysis and spatio-temporal expression profiling showed that HaFDL exists as a soluble homo-tetrameric form, exhibits a broad substrate affinity and is involved in the JH-specific farnesol oxidation in H. armigera . Additionally, the study presents the first crystal structure of the HaFDL-NADP enzyme complex determined at 1.6 Å resolution. Structural analysis revealed that HaFDL belongs to the NADP-specific cP2 subfamily of the classical short-chain dehydrogenase/reductase (SDR) family and exhibits typical structural features of those enzymes including the conserved nucleotide-binding Rossman-fold. The isothermal titration calorimetry (ITC) showed a high binding affinity (dissociation constant, Kd, 3.43 μM) of NADP to the enzyme. Comparative structural analysis showed a distinct substrate-binding pocket (SBP) loop with a spacious and hydrophobic substrate-binding pocket in HaFDL, consistent with the biochemically observed promiscuous substrate specificity. Finally, based on the crystal structure, substrate modeling and structural comparison with homologs, a two-step reaction mechanism is proposed. Overall, the findings significantly impact and contribute to our understanding of farnesol dehydrogenase functional properties in JH biosynthesis in H. armigera . Graphical abstract: Image 1 Highlights: Determination of first crystal structure of insect farnesol dehydrogenase complexed with NADP at 1.6 Å resolution. HaFDL has varied tissue-wide transcript abundance and a broad range of substrate affinity. Preferential binding of NADP by HaFDL enzyme at Kd of 3.43 μM. The findings may aid in developing structure-guided insect-growth regulatory molecules.